1986
DOI: 10.1007/bf00419598
|View full text |Cite
|
Sign up to set email alerts
|

Direct in vitro action of thyroid hormones on mitochondrial RNA-polymerase

Abstract: The authors show the direct in vitro action of thyroid hormones on RNA-polymerase activity in rat liver mitochondria. 3,5,3' L-triiodothyronine (L-T3) and 3,5,3',5' L-tetraiodothyronine (L-T4) stimulate mitochondrial RNA synthesis without either increasing the permeability of preswollen mitochondria or stimulating the synthesis of the triphosphate ribonucleotides (NTP's). Thyroid hormones do not directly depress mitochondrial RNA hydrolysis. Studies carried out with structural analogues of thyroid hormones ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Last, in organello transcription experiments demonstrated that p43 strongly increases mitochondrial genome transcription, and, as a consequence, mitochondrial protein synthesis (Casas et al 1999). In agreement with Martino et al (1986), this influence was detected as soon as the hormone had been present for 5 min. Complementary studies were performed in cultured cells.…”
Section: Thyroid Hormone Influence On Mitochondrial Genome Expressionsupporting
confidence: 83%
See 1 more Smart Citation
“…Last, in organello transcription experiments demonstrated that p43 strongly increases mitochondrial genome transcription, and, as a consequence, mitochondrial protein synthesis (Casas et al 1999). In agreement with Martino et al (1986), this influence was detected as soon as the hormone had been present for 5 min. Complementary studies were performed in cultured cells.…”
Section: Thyroid Hormone Influence On Mitochondrial Genome Expressionsupporting
confidence: 83%
“…However, studies using isolated mitochondria from hypothyroid or control rat liver led to the conclusion that this mechanism was not exclusive. First, Martino et al (1986) observed that in vitro addition of T3 stimulates mt-RNA polymerases in the absence of nuclear influence, with a latency period of less than 5 min. Secondly, Enriquez et al (1999) demonstrated that addition of minute amounts of the hormone to isolated mitochondria influenced mitochondrial transcription, and particularly the mRNA/rRNA ratio, in relation to changes in the pattern of protein binding to the mitochondrial genome.…”
Section: Thyroid Hormone Influence On Mitochondrial Genome Expressionmentioning
confidence: 99%
“…While the maximal influence requires several hours, this action is initiated after a latency period of several minutes in isolated mitochondria. 11 As T3 increases the steady‐state level of mt‐TFA mRNA, 12 a constitutive mitochondrial transcription factor 13 encoded by a nuclear gene, several investigators consider this action to be induced at the nuclear level. However, this hypothesis is not fully supported by the very short‐term effect recorded in isolated mitochondria.…”
Section: The Influence Of T3 Upon Mitochondrial Activitymentioning
confidence: 99%
“…However, this hypothesis is not fully supported by the very short‐term effect recorded in isolated mitochondria. 11…”
Section: The Influence Of T3 Upon Mitochondrial Activitymentioning
confidence: 99%
“…Moreover, T3 is considered as the major regulator of mitochondrial biogenesis (Mutvei et al, 1989). Its influence upon mitochondrial protein synthesis (Freeman et al, 1963), mitochondriogenesis (De Leo et al, 1976), oxydative phosphorylations (Sterling et al, 1977;, and mitochondrial gene expression (De Leo et al, 1976;Martino et al, 1986) is well established. The identification of a T3 mitochondrial receptor belonging to the c-erb A family in the mitochondrial matrix is probably a major key to understanding the T3 action at the mitochondrial level.…”
mentioning
confidence: 98%